Organic silicon synthetic leather and preparation method thereof

By introducing polyurethane and hyperbranched polysiloxane grafted silica into the surface coating of the silicone synthetic leather to form a dual crosslinking system, the shortcomings of the silicone synthetic leather in wear resistance and sebum resistance are solved, and its comprehensive performance is significantly improved.

CN119711210APending Publication Date: 2025-03-28ZHEJIANG XINAN CHONGYAO NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510138421.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing silicone synthetic leather has a high wear rate under dynamic friction conditions, and is prone to sticky touch when it comes into contact with the human sebum environment for a long time, making it difficult to improve wear resistance and sebum resistance at the same time.

Method used

By introducing polyurethane into silicone rubber, a silicone-polyurethane dual crosslinking system is formed to enhance the density and hardness of the surface protective layer, and the fracture toughness and crack resistance of the silicon dioxide grafted through hyperbranched polysiloxane are enhanced.

Benefits of technology

The wear resistance and sebum resistance of synthetic leather has been significantly improved. The Taber wear amount has been reduced to 8-10 mg, the sebum adsorption amount has been reduced by more than 50%, and there is no sticky feeling for 500 hours, and the elongation rate of break is increased to 220-260%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005264001650000141
    Figure BDA0005264001650000141
  • Figure BDA0005264001650000142
    Figure BDA0005264001650000142
  • Figure BDA0005264001650000151
    Figure BDA0005264001650000151
Patent Text Reader

Abstract

The invention discloses organic silicon synthetic leather and a preparation method thereof. The synthetic leather comprises base cloth, a silicone rubber layer and a surface coating layer, wherein the surface coating layer is prepared from the following raw materials in parts by weight: 20-70 parts of vinyl terminated polysiloxane, 5-30 parts of hydrogen-containing polysiloxane, 0.5-3 parts of a reaction inhibitor, 0.1-1 part of a platinum catalyst, 5-50 parts of silicon dioxide, 10-60 parts of silicon dioxide microspheres, 5-100 parts of cyclic siloxane, 10-50 parts of a polyurethane prepolymer, 2-10 parts of a polyisocyanate curing agent and 1-10 parts of a compatilizer; the polyurethane prepolymer is obtained by reacting polyhydric alcohol, hydroxyl-terminated polysiloxane and polyisocyanate according to the mass ratio of (60 to 80): (5 to 25): (15 to 25). The polyurethane is introduced into the silicone rubber to generate a synergistic effect, so that the compactness and hardness of a surface protection layer are improved, and the problem that the current organic silicon synthetic leather is poor in wear resistance and sebum resistance is effectively relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of synthetic leather, and in particular to an organosilicon synthetic leather and a preparation method thereof. Background Art

[0002] The application of silicone materials in the field of synthetic leather has developed rapidly in recent years. Its unique polysiloxane structure gives synthetic leather excellent hydrophobicity, temperature resistance and biocompatibility. In the prior art, by compounding silicone polymers with base fabrics to form a three-dimensional network structure, a dense protective layer can be formed on the surface of synthetic leather, significantly improving the tear resistance and chemical corrosion resistance of the product. In specific fields such as medical protection, automotive accessories, and sports equipment coatings, silicone synthetic leather has shown the potential to replace traditional PVC / PU materials, especially in terms of recyclability and VOC emission control. It has significant environmental advantages.

[0003] However, although silicone materials have shown significant advantages in the field of synthetic leather, there are still technical bottlenecks that need to be solved in practical applications. Conventional silicone rubber systems have a high wear rate under dynamic friction conditions. When the friction coefficient exceeds 0.8, the initiation and expansion of surface microcracks will cause the protective layer to fail quickly. In addition, when exposed to the human sebum environment for a long time, the siloxane main chain is easily physically adsorbed with fatty acid substances, causing the surface energy to increase and causing a sticky touch. This phenomenon is particularly obvious after the contact time exceeds 200 hours. Therefore, how to break through the synergistic improvement of wear resistance and anti-sebum performance while maintaining the inherent properties of silicone has become a key challenge for technological innovation in this field. Summary of the invention

[0004] The present application provides a silicone synthetic leather and a preparation method thereof, which introduces polyurethane into silicone rubber to produce a synergistic effect, thereby improving the density and hardness of the surface protective layer, and effectively alleviating the problem that the current silicone synthetic leather has poor performance in wear resistance and anti-sebum performance.

[0005] In a first aspect, the present application provides an organosilicon synthetic leather, comprising a base fabric, a silicone rubber layer and a topcoat layer, wherein the raw materials of the topcoat layer comprise the following components in parts by weight:

[0006] 20-70 parts of vinyl-terminated polysiloxane, 5-30 parts of hydrogen-containing polysiloxane, 0.5-3 parts of reaction inhibitor, 0.1-1 parts of platinum catalyst, 5-50 parts of silica, 10-60 parts of silica microbeads, 5-100 parts of cyclic siloxane, 10-50 parts of polyurethane prepolymer, 2-10 parts of polyisocyanate curing agent, and 1-10 parts of compatibilizer;

[0007] The polyurethane prepolymer is obtained by reacting polyol, terminal hydroxyl polysiloxane and polyisocyanate in a mass ratio of (60-80):(5-25):(15-25).

[0008] It should be noted that the vinyl-terminated polysiloxane refers to silicone oil having at least one vinyl terminal group, and the hydrogen-containing polysiloxane refers to silicone oil having at least one silicon hydrogen group. The vinyl-terminated polysiloxane and the hydrogen-containing polysiloxane can undergo addition reaction under a platinum catalyst.

[0009] Exemplarily, the reaction inhibitor is selected from one or more of 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, 1,1,3,3-tetramethyl-1,3-divinylsiloxane, 3-methyl-1-butyn-3-ol, 1-ethynylcyclohexanol, 3-phenyl-1-butyn-3-ol, 3-propyl-1-butyn-3-ol and 3-octyl-1-butyn-3-ol.

[0010] Exemplarily, the platinum catalyst is one or more of an alcohol solution of chloroplatinic acid, a platinum catalyst coordinated with tetrahydrofuran, and a platinum catalyst coordinated with divinyltetramethylsiloxane.

[0011] Exemplarily, the cyclic siloxane is selected from cyclotetrasiloxane and / or cyclopentasiloxane.

[0012] The present application introduces a polyurethane prepolymer and a polyisocyanate curing agent into the surface coating of the silicone synthetic leather to construct a silicone-polyurethane dual cross-linking system, thereby achieving a synergistic improvement in wear resistance and anti-sebum performance.

[0013] First, the interpenetrating structure of the polyurethane hard segment and the silicone network enhances the mechanical strength of the coating. The urethane bond (-NHCOO-) in the polyurethane prepolymer molecular chain forms a rigid hard segment micro-region, and the introduction of terminal hydroxyl polysiloxane makes the polyurethane chain end have a siloxane group (-Si-O-Si-). During the curing stage, the polyurethane phase and the silicone phase react separately to construct a cross-linked network, and the two phases form an interpenetrating structure (IPN) through the bridging effect of the terminal hydroxyl polysiloxane. The polyurethane hard segment acts as a "support skeleton" to disperse stress, and the silicone soft segment absorbs energy through chain segment slippage, so that the coating can resist plastic deformation during friction and dissipate energy through deformation, thereby reducing the dynamic friction coefficient and significantly reducing the wear rate.

[0014] Secondly, the surface energy is regulated to inhibit the adsorption of sebum by synthetic leather. Although the hydrophobicity of the silicone main chain can resist water-based stains, its low-polarity surface is prone to adsorb non-polar sebum molecules through van der Waals forces. The introduction of polyurethane can utilize the surface energy difference between the polar urethane groups in the molecular chain and silicone to form a microscopic polarity gradient, making the overall surface energy of the coating lower than the surface energy of sebum to reduce adsorption, and higher than pure silicone to reduce stickiness.

[0015] In any of the above technical solutions, the weight ratio of the vinyl-terminated polysiloxane to the polyurethane prepolymer is 65-75:25-35.

[0016] In any of the above technical solutions, the number average molecular weight of the terminal hydroxyl polysiloxane is 3000 to 20000.

[0017] The polyol is selected from polyether polyol or polycarbonate polyol, and the number average molecular weight is 2000-5000; the polyisocyanate is hexamethylene diisocyanate trimer or isophorone diisocyanate.

[0018] It should be noted that the raw materials of the polyurethane prepolymer have a high content of polyol soft segments within the above ratio range (the soft segments account for 60-80%) and high flexibility. The selection of long-chain flexible polyols (such as polyether polyol PTMG, polycarbonate diol PCDL) with a number average molecular weight controlled at 2000-5000 can reduce the glass transition temperature (Tg) and enhance the mobility of the chain segments.

[0019] In any of the above technical solutions, the compatibilizer is an aminosilane coupling agent and a polyethylene oxide-polydimethylsiloxane block copolymer in a mass ratio of 1:2 to 3.

[0020] The above compatibilizer can improve the compatibility of the two phases through the dual mechanisms of chemical bonding and physical entanglement. Aminosilane has good affinity with the two phases and can form chemical bonds with the two phases respectively; while the polyethylene oxide segment (hydrophilic) of the polyethylene oxide-polydimethylsiloxane block copolymer (PEO-PDMS) is compatible with polyurethane, and the PDMS segment (hydrophobic) is compatible with silicone, forming an interfacial transition layer. This improves the interfacial bonding energy of the two phases and avoids performance degradation caused by phase separation during long-term use.

[0021] In any of the above technical solutions, the silicon dioxide is hyperbranched polysiloxane grafted silicon dioxide, and the preparation method is as follows:

[0022] SiO2 is vacuum dried at 110-140°C, dispersed in toluene, triethylamine is added, and ultrasonic treatment is performed; amino hyperbranched polysiloxane is added, the temperature is raised to 70-90°C under nitrogen protection, the reaction is stirred for 20-30 hours, and the product is obtained by filtering, washing, and drying.

[0023] The present application introduces a polyurethane system into the organosilicon phase, which improves the wear resistance and anti-sebum performance of the surface coating, while also increasing the brittleness of the coating and reducing the elastic touch. To overcome this problem, the present application grafts silica with the above-mentioned amino hyperbranched polysiloxane (HBPS). On the one hand, the grafted silica can form a ternary interface with the organosilicon phase and the polyurethane phase. This bridging effect causes the two phases to deform synergistically. Under the action of external forces, the rigid support of the PU hard segment and the flexible deformation of the organosilicon jointly consume energy, thereby improving the fracture toughness. On the other hand, the three-dimensional branched structure of HBPS forms a large number of molecular chain entanglement points inside the material. When the coating is impacted by external forces, the stretching and slippage of the branched chains absorb energy. At the same time, the gaps (free volumes) between the branched chains allow local deformation, disperse stress through hole expansion, and inhibit crack propagation.

[0024] In any of the above technical solutions, the average particle size of the silica is 10 to 50 nm, and the average particle size of the silica microbeads is 1 to 20 μm.

[0025] Silica microbeads (1-20 μm) and hyperbranched polysiloxane grafted silica (10-50 nm) form a multi-scale rough surface, which reduces the actual contact area through physical morphology effects, increases the sebum contact angle, and reduces the amount of sebum adsorption by more than 50%.

[0026] In any of the above technical solutions, the silicone rubber layer is prepared by addition reaction of vinyl-terminated polysiloxane and hydrogen-containing polysiloxane in the presence of a platinum catalyst.

[0027] In a second aspect, the present application provides a method for preparing silicone synthetic leather, characterized in that the following operations are performed according to any of the above-mentioned raw material ratios:

[0028] Vinyl-terminated polysiloxane, hydrogen-containing polysiloxane, platinum catalyst, silica, silica microbeads, and cyclic siloxane are mixed and dispersed to form an organic silicon phase; polyurethane prepolymer, polyisocyanate curing agent, and compatibilizer are mixed to form a polyurethane phase; the organic silicon phase and the polyurethane phase are blended at a temperature not higher than 40° C. and homogenized for 10 to 30 minutes to obtain a surface coating;

[0029] Applying a surface coating on a release paper with a specific pattern to form a surface coating with a thickness of 3 to 30 microns;

[0030] The silicone rubber is made into a film and coated on a base fabric to form a base fabric with a silicone rubber layer;

[0031] The surface coating is laminated to the base fabric with the silicone rubber coating, and then the laminated organic silicone rubber is cured.

[0032] In any of the above technical solutions, the curing includes first curing at 80-100° C. for 5-30 minutes, and then curing at 130-180° C. for 1-10 minutes.

[0033] Finally, the staged curing process optimizes the network formation dynamics. The first stage (80-100°C) preferentially activates the -NCO and -OH reactions of the polyurethane to form a preliminary cross-linked network; the second stage (120-150°C) promotes the Si-H and Si-Vi addition reactions of the silicone, while allowing the polyurethane hard segment micro-regions to be arranged in an orderly manner. This process ensures that the two-phase network is cross-linked synchronously and does not interfere with each other, ultimately forming a dual-continuous phase structure, which improves the elastic toughness of the coating.

[0034] In any of the above technical solutions, the coating is carried out by spraying, roller coating, knife coating, plasma coating, etc.

[0035] In any of the above technical solutions, the base fabric includes but is not limited to woven fabric, knitted fabric, and non-woven fabric, and the fiber type of the fabric is selected from natural fiber, synthetic fiber or regenerated fiber.

[0036] In summary, this application has the following beneficial effects:

[0037] The technical solution of this application significantly improves the comprehensive performance of synthetic leather through the synergistic compounding of silicone and polyurethane (PU) and the introduction of hyperbranched polysiloxane grafted silica (HBPS-SiO2). The flexible network of silicone and the rigid hard segment of PU form an interpenetrating structure, which improves the wear resistance by 40% to 50%, and the Taber wear loss is as low as 8 to 10 mg; the surface energy gradient design and micro-nano rough structure significantly reduce the amount of sebum adsorption, and there is no sticky feeling for 500 hours. HBPS-SiO2 compensates for the brittleness of PU through chemical bonding and branched chain entanglement, and the elongation at break is increased to 220% to 260%. DETAILED DESCRIPTION

[0038] Preparation Example

[0039] Preparation Example 1-1, a polyurethane prepolymer is prepared according to the following method:

[0040] 80g of polyether diol (Mn=5000) and 5g of dihydroxy-terminated polysiloxane (Mn=3000) were added to a reactor, heated to 100°C under nitrogen protection, and vacuum dehydrated for 2 hours (vacuum degree -0.095MPa) until the moisture content was ≤0.05%. The temperature was lowered to 80°C, 15g of hexamethylene diisocyanate trimer was slowly added dropwise, and the reaction was stirred at a constant temperature for 3 hours, during which the NCO content was monitored (theoretical value 6.5%). The reaction was stopped when the NCO content reached 6.3% to 6.7%, and the mixture was cooled to room temperature to obtain a transparent viscous prepolymer.

[0041] Preparation Example 1-2, a polyurethane prepolymer is prepared according to the following method:

[0042] 60g polycarbonate diol (Mn=2000) and 20g dihydroxy-terminated polysiloxane (Mn=20000) were added to the reactor, heated to 110°C under nitrogen protection, and vacuum dehydrated for 2 hours (vacuum degree -0.095MPa) until the moisture content was ≤0.03%. The temperature was lowered to 75°C, 25g isophorone diisocyanate was slowly added dropwise, and the reaction was stirred at a constant temperature for 4 hours, during which the NCO content was monitored (theoretical value 8.2%). The reaction was stopped when the NCO content reached 8.0% to 8.4%, and cooled to room temperature to obtain a transparent viscous prepolymer.

[0043] Preparation Example 1-3, a polyurethane prepolymer, is prepared according to the following method:

[0044] 70g of polycarbonate diol (Mn=3500) and 15g of dihydroxy-terminated polysiloxane (Mn=10000) were added to a reactor, heated to 105°C under nitrogen protection, and vacuum dehydrated for 2.5 hours (vacuum degree -0.095MPa) until the moisture content was ≤0.05%. The temperature was lowered to 85°C, and 20g of hexamethylene diisocyanate trimer was slowly added dropwise, and the reaction was stirred at a constant temperature for 3 hours, during which the NCO content was monitored (theoretical value 7.8%). The reaction was stopped when the NCO content reached 7.6% to 8.0%, and the mixture was cooled to room temperature to obtain a transparent viscous prepolymer.

[0045] Preparation Example 1-4, a polyurethane prepolymer, differs from Preparation Example 1-1 in that an equal amount of polyether diol (Mn=5000) is used to replace the dihydroxy-terminated polysiloxane (Mn=3000).

[0046] Preparation Example 2-1, a hyperbranched polysiloxane grafted silica, was prepared according to the following method:

[0047] Preparation of HBPS: Add 50g KH-550 and 30g methyltrimethoxysilane to 100g ethanol, stir and mix evenly, slowly drop 5g hydrochloric acid (0.1mol) and 20g deionized water, hydrolyze at 25°C, and react for 4 hours. Heat to 60°C, continue stirring for 10 hours for polycondensation reaction, and control the pH to 3-4 during the reaction. The reaction product is precipitated with ethanol 3 times and vacuum dried (50°C / 24h) to obtain white powdery hyperbranched polysiloxane (HBPS).

[0048] Preparation of HBPS-SiO2 composite particles: 100g of silica powder (average particle size 20nm) was vacuum dried at 120℃ for 6 hours to remove surface adsorbed water. The dried silica was dispersed in 200g of toluene, 5g of triethylamine was added, and ultrasonic treatment was performed for 30 minutes. 30g of the above-prepared HBPS was added, the temperature was raised to 80℃ under nitrogen protection, and the reaction was stirred for 24 hours. The silica was separated by centrifugation, washed with toluene 3 times, and vacuum dried at 60℃.

[0049] Preparation Example 2-2, a hyperbranched polysiloxane grafted silica, was prepared according to the following method:

[0050] Preparation of HBPS: Add 70g KH-550 and 40g methyltrimethoxysilane to 150g ethanol, stir and mix evenly, slowly drop 6.5g hydrochloric acid (0.1mol) and 25g deionized water, hydrolyze at 25°C, and react for 4 hours. Heat to 70°C, continue stirring for 8 hours for polycondensation reaction, and control the pH to 3-4 during the reaction. The reaction product is precipitated with ethanol 3 times and vacuum dried (50°C / 24h) to obtain white powdery hyperbranched polysiloxane (HBPS).

[0051] Preparation of HBPS-SiO2 composite particles: 100g of silica powder (average particle size 20nm) was vacuum dried at 130℃ for 6 hours to remove surface adsorbed water. The dried silica was dispersed in 200g of toluene, 5g of triethylamine was added, and ultrasonic treatment was performed for 30 minutes. 25g of the above-prepared HBPS was added, the temperature was raised to 80℃ under nitrogen protection, and the reaction was stirred for 24 hours. The silica was separated by centrifugation, washed with toluene 3 times, and vacuum dried at 60℃.

[0052] Preparation Example 2-3, a hyperbranched polysiloxane grafted silica, was prepared according to the following method:

[0053] Preparation of HBPS: Add 50g KH-550 and 20g methyltrimethoxysilane to 100g ethanol, stir and mix evenly, slowly drop 4g hydrochloric acid (0.1mol) and 15g deionized water, hydrolyze at 25°C, and react for 3 hours. Heat to 60°C, continue stirring for 8 hours for polycondensation reaction, and control the pH to 3-4 during the reaction. The reaction product is precipitated with ethanol 3 times and vacuum dried (50°C / 24h) to obtain white powdery hyperbranched polysiloxane (HBPS).

[0054] Preparation of HBPS-SiO2 composite particles: 100g of silica powder (average particle size 20nm) was vacuum dried at 120℃ for 6 hours to remove surface adsorbed water. The dried silica was dispersed in 200g of toluene, 5g of triethylamine was added, and ultrasonic treatment was performed for 30 minutes. 35g of the above-prepared HBPS was added, the temperature was raised to 80℃ under nitrogen protection, and the reaction was stirred for 20 hours. The silica was separated by centrifugation, washed with toluene 3 times, and vacuum dried at 60℃.

[0055] Example

[0056] Example 1, a silicone synthetic leather, is prepared according to the following steps:

[0057] Raw material ratio: vinyl-terminated polysiloxane 65kg (number average molecular weight 20000, vinyl content 0.5mol%), hydrogen-containing polysiloxane 10kg (hydrogen content 1.2wt%), reaction inhibitor 1.5kg (1-ethynylcyclohexanol), divinyltetramethylsiloxane coordinated platinum catalyst 0.5kg, hyperbranched polysiloxane grafted silica 15kg of Preparation Example 2-1, silica microbeads (average particle size 5μm) 25kg, cyclic siloxane (D4) 30kg, polyurethane prepolymer 30kg of Preparation Example 1-1, polyisocyanate curing agent (IPDI) 5kg, aminosilane coupling agent (KH-550) 1.2kg, polyethylene oxide-polydimethylsiloxane block copolymer (PEO accounted for 30%) 3kg.

[0058] Preparation of silicone phase: vinyl-terminated polysiloxane, hydrogen-containing polysiloxane, platinum catalyst, silica, silica microbeads, and cyclic siloxane were added into a planetary mixer (vacuum degree - 0.09 MPa), dispersed at high speed (1500 rpm) at 30 °C for 20 min, and dispersed at high speed (1500 rpm) at 30 °C for 20 min to form a uniform slurry.

[0059] Preparation of polyurethane phase: Mix the polyurethane prepolymer with the polyisocyanate curing agent and the compatibilizer, and stir at a low speed for 10 minutes (500 rpm).

[0060] Preparation of surface coating: The silicone phase and the polyurethane phase were blended at 35°C and homogenized for 15 minutes (vacuum degree -0.08 MPa).

[0061] Coating and lamination: Apply the surface coating (wet film thickness 25 μm) on the embossed release paper and pre-cure at 80°C for 15 minutes; LR 3003 / 50) is formed into a film (thickness 0.5mm) by a calender and bonded to a polyester base fabric (weight 200g / m 2 ), and then bonded with the surface coating.

[0062] Curing: First cure at 90℃ for 20 minutes, then cure at 150℃ for 5 minutes, and peel off the release paper after cooling.

[0063] Example 2, a silicone synthetic leather, is prepared according to the following steps:

[0064] Raw material ratio: vinyl-terminated polysiloxane 45kg (number average molecular weight 50000, vinyl content 0.8mol%), hydrogen-containing polysiloxane 18kg (hydrogen content 0.5wt%), reaction inhibitor 0.8kg (3-methyl-1-butyn-3-ol), divinyltetramethylsiloxane coordinated platinum catalyst 0.3kg, hyperbranched polysiloxane grafted silica 30kg of Preparation Example 2-2, silica microbeads (average particle size 10μm) 40kg, cyclic siloxane (D4) 60kg, polyurethane prepolymer 20kg of Preparation Example 1-2, polyisocyanate curing agent (HDI) 3kg, aminosilane coupling agent (KH-792) 0.7kg, polyethylene oxide-polydimethylsiloxane block copolymer (PEO accounts for 50%) 1.3kg.

[0065] Preparation of silicone phase: vinyl-terminated polysiloxane, hydrogen-containing polysiloxane, platinum catalyst, silica, silica microbeads, and cyclic siloxane were added into a planetary mixer (vacuum degree - 0.09 MPa) and dispersed at high speed (1500 rpm) at 30°C for 20 minutes to form a uniform slurry.

[0066] Preparation of polyurethane phase: Mix the polyurethane prepolymer with the polyisocyanate curing agent and the compatibilizer, and stir at a low speed for 10 minutes (500 rpm).

[0067] Preparation of surface coating: The silicone phase and the polyurethane phase were blended at 40°C and homogenized for 20 minutes (vacuum degree -0.08 MPa).

[0068] Coating and lamination: Apply the surface coating (wet film thickness 25 μm) on the embossed release paper and pre-cure at 80°C for 15 minutes; LR 3003 / 50) is formed into a film (thickness 0.5mm) by a calender and bonded to a polyester base fabric (weight 200g / m 2 ), and then bonded with the surface coating.

[0069] Curing: First cure at 100℃ for 10 minutes, then cure at 130℃ for 8 minutes, and peel off the release paper after cooling.

[0070] Embodiment 3, a kind of organosilicon synthetic leather is prepared by the following steps:

[0071] Raw material ratio: vinyl-terminated polysiloxane 25kg (number average molecular weight 8000, vinyl content 1.2mol%), hydrogen-containing polysiloxane 25kg (hydrogen content 1.5wt%), reaction inhibitor 2.5kg (1-ethynylcyclohexanol), divinyltetramethylsiloxane coordinated platinum catalyst 0.8kg, hyperbranched polysiloxane grafted silica 40kg of Preparation Example 2-3, silica microbeads (average particle size 15μm) 50kg, cyclic siloxane (D5) 80kg, polyurethane prepolymer 45kg of Preparation Example 1-3, polyisocyanate curing agent (IPDI) 8kg, aminosilane coupling agent (KH-570) 2kg, polyethylene oxide-polydimethylsiloxane block copolymer (PEO accounts for 20%) 5kg.

[0072] Preparation of silicone phase: vinyl-terminated polysiloxane, hydrogen-containing polysiloxane, platinum catalyst, silica, silica microbeads, and cyclic siloxane were added into a planetary mixer (vacuum degree - 0.09 MPa), dispersed at high speed (1500 rpm) at 30 °C for 20 min, and dispersed at high speed (1500 rpm) at 30 °C for 20 min to form a uniform slurry.

[0073] Preparation of polyurethane phase: Mix the polyurethane prepolymer with the polyisocyanate curing agent and the compatibilizer, and stir at a low speed for 10 minutes (500 rpm).

[0074] Preparation of surface coating: The silicone phase and the polyurethane phase were blended at 30°C and homogenized for 25 minutes (vacuum degree -0.08 MPa).

[0075] Coating and lamination: Apply the surface coating (wet film thickness 25 μm) on the embossed release paper and pre-cure at 80°C for 15 minutes; LR 3003 / 50) is formed into a film (thickness 0.5mm) by a calender and bonded to a polyester base fabric (weight 200g / m 2 ), and then bonded with the surface coating.

[0076] Curing: First cure at 85℃ for 25 minutes, then cure at 160℃ for 8 minutes, and peel off the release paper after cooling.

[0077] Example 4 is a silicone synthetic leather, which is different from Example 1 in that the polyethylene oxide-polydimethylsiloxane block copolymer (PEO accounts for 30%) is replaced by an equal amount of aminosilane coupling agent (KH-550) in the compatibilizer.

[0078] Example 5, a silicone synthetic leather, is different from Example 1 in that the aminosilane coupling agent (KH-550) is replaced by an equal amount of polyethylene oxide-polydimethylsiloxane block copolymer (PEO accounts for 30%) in the compatibilizer.

[0079] Example 6, a silicone synthetic leather, is different from Example 1 in that an equal amount of aminosilane-modified silica (average particle size 20 nm) is used to replace the hyperbranched polysiloxane-grafted silica of Preparation Example 2-1 in the preparation of the silicone phase. The preparation method of the aminosilane-modified silica is as follows: 3-aminopropyltriethoxysilane and anhydrous ethanol are mixed in a volume ratio of 1:9, stirred evenly, a small amount of acetic acid is added to control the pH value to 5, an aminosilane solution is obtained, and dry silica is added. The mass ratio of silica to APTES is about 10:1. Magnetic stirring is carried out at 60°C for 6 hours. After the reaction is completed, centrifugation is performed and the unreacted silane is removed by washing 3 times with anhydrous ethanol. The modified silica is dried at 60°C for 12 hours.

[0080] Comparative Example

[0081] Comparative Example 1 is a silicone synthetic leather, which is different from Example 1 in that the polyurethane prepolymer of Preparation Example 1-1 is replaced by an equal amount of the polyurethane prepolymer of Preparation Example 1-4 in the preparation of the silicone phase.

[0082] Comparative Example 2 is a silicone synthetic leather, which is different from Example 1 in that the raw materials of the surface coating layer do not contain a polyurethane phase. The specific steps are as follows:

[0083] Raw material ratio: vinyl-terminated polysiloxane 65kg (number average molecular weight 20000, vinyl content 0.5mol%), hydrogen-containing polysiloxane 10kg (hydrogen content 1.2wt%), reaction inhibitor 1.5kg (1-ethynylcyclohexanol), divinyltetramethylsiloxane coordinated platinum catalyst 0.5kg, aminosilane-modified silica (average particle size 20nm) 15kg, silica microbeads (average particle size 5μm) 25kg, cyclic siloxane (D4) 30kg.

[0084] Preparation of surface coating: vinyl-terminated polysiloxane, hydrogen-containing polysiloxane, platinum catalyst, silica, silica microbeads, and cyclic siloxane were added into a planetary mixer (vacuum degree - 0.09 MPa), dispersed at high speed (1500 rpm) at 30 °C for 20 min, and dispersed at high speed (1500 rpm) at 30 °C for 20 min to form a uniform slurry.

[0085] Coating and lamination: Apply the surface coating (wet film thickness 25 μm) on the embossed release paper and pre-cure at 80°C for 15 minutes; LR 3003 / 50) is formed into a film (thickness 0.5mm) by a calender and bonded to a polyester base fabric (weight 200g / m 2 ), and then bonded with the surface coating.

[0086] Curing: First cure at 90℃ for 20 minutes, then cure at 150℃ for 5 minutes, and peel off the release paper after cooling.

[0087] Performance testing

[0088] 1. Wear resistance test

[0089] Test method: Test according to ASTM D4060-19 Taber abrasion test, using H-18 grinding wheel, load 500g, rotate 1000 times, measure the wear mass loss, unit mg.

[0090]

[0091] Result analysis: Compared with comparative examples 1-2, the polyurethane-silicone interpenetrating network of examples 1-3 significantly improved the wear resistance of the surface coating, with Taber abrasion loss ≤ 10.1 mg. Examples 4-5 had incomplete compatibilizers. The interface bonding was weakened, and the wear resistance gradually decreased. Example 6 used unmodified SiO2, lacked the interface bridging of hyperbranched polysiloxane, and the wear resistance was deteriorated, and the abrasion loss increased to 16.5 mg.

[0092] 2. Anti-sebum performance test

[0093] (1) Oil resistance: Oil resistance test was performed according to AATCC 118-2019, with a score range of 1 to 8, with 8 being the best.

[0094] (2) Sebum adsorption: artificial sebum (ingredients: 30% squalene, 40% triglyceride, 30% free fatty acid) was soaked in water at 37°C for 200 h and weighed (unit: mg / cm).

[0095] (3) After immersion in artificial sebum for 500 hours (37°C / humidity 60%), the touch was rated on a scale of 1 to 5, with 5 = no stickiness. The average of the ratings was taken.

[0096]

[0097] Result analysis: The micro-nano rough surface (HBPS-SiO2+silica microbeads) and polarity gradient design of Examples 1-3, the compatibilizer (KH-550+PEO-PDMS) maintained the interface stability, the oil resistance score was ≥7, and the sebum adsorption was ≤0.18mg / cm 2 , the touch score is ≥4.5. In Example 4-5, due to the incomplete compatibilizer, the interface phase separation was caused, the surface energy gradient was destroyed, and the oil resistance was significantly reduced. In Example 6, unmodified SiO2 was used, resulting in an increase in surface energy (lack of hydrophobic modification of HBPS), and the adsorption amount was as high as 0.41 mg / cm 2 , it feels sticky.

[0098] 3. Mechanical properties test

[0099] (1) Tensile properties: The test was conducted according to ASTM D638-14, using dumbbell-shaped specimens at a tensile rate of 500 mm / min.

[0100] (2) Impact strength: tested according to ISO 179-1:2010 simply supported beam impact test.

[0101]

[0102] Result analysis: Compared with Example 6, the HBPS-SiO2 used in Examples 1-3 improves the toughness of the coating through branched chain entanglement and interface bridging, with elongation at break ≥ 220% and impact strength ≥ 14 kJ / m 2 .

[0103] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An organosilicon synthetic leather, comprising a base fabric, a silicone rubber layer and a surface coating layer, characterized in that: The raw materials of the topcoat layer include the following components in parts by weight: 20-70 parts of vinyl-terminated polysiloxane, 5-30 parts of hydrogen-containing polysiloxane, 0.5-3 parts of reaction inhibitor, 0.1-1 parts of platinum catalyst, 5-50 parts of silica, 10-60 parts of silica microbeads, 5-100 parts of cyclic siloxane, 10-50 parts of polyurethane prepolymer, 2-10 parts of polyisocyanate curing agent, and 1-10 parts of compatibilizer; The polyurethane prepolymer is obtained by reacting polyol, terminal hydroxyl polysiloxane and polyisocyanate in a mass ratio of (60-80):(5-25):(15-25).

2. The organic silicon synthetic leather according to claim 1, characterized in that: The weight ratio of the vinyl-terminated polysiloxane to the polyurethane prepolymer is 65-75:25-35.

3. The organic silicon synthetic leather according to claim 1, characterized in that: The number average molecular weight of the terminal hydroxyl polysiloxane is 3,000 to 20,000.

4. The organic silicon synthetic leather according to claim 1, characterized in that: The polyol is selected from polyether polyol or polycarbonate polyol, and the number average molecular weight is 2000-5000; the polyisocyanate is hexamethylene diisocyanate trimer or isophorone diisocyanate.

5. The organic silicon synthetic leather according to claim 1, characterized in that: The compatibilizer is an aminosilane coupling agent and a polyethylene oxide-polydimethylsiloxane block copolymer in a mass ratio of 1:2-3.

6. The organosilicon synthetic leather according to claim 1, characterized in that: The silicon dioxide is hyperbranched polysiloxane grafted silicon dioxide, and the preparation method is as follows: SiO2 is vacuum dried at 110-140°C, dispersed in toluene, triethylamine is added, and ultrasonic treatment is performed; amino hyperbranched polysiloxane is added, the temperature is raised to 70-90°C under nitrogen protection, the reaction is stirred for 20-30 hours, and the product is obtained by filtering, washing, and drying.

7. The organic silicon synthetic leather according to claim 1, characterized in that: The average particle size of the silicon dioxide is 10 to 50 nm, and the average particle size of the silicon dioxide microbeads is 1 to 20 μm.

8. The organosilicon synthetic leather according to claim 1, characterized in that: The silicone rubber layer is prepared by addition reaction of vinyl-terminated polysiloxane and hydrogen-containing polysiloxane in the presence of a platinum catalyst.

9. A method for preparing silicone synthetic leather, characterized in that: According to any one of claims 1 to 8, the following steps are performed: Vinyl-terminated polysiloxane, hydrogen-containing polysiloxane, platinum catalyst, silica, silica microbeads, and cyclic siloxane are mixed and dispersed to form an organic silicon phase; polyurethane prepolymer, polyisocyanate curing agent, and compatibilizer are mixed to form a polyurethane phase; the organic silicon phase and the polyurethane phase are blended at a temperature not higher than 40° C. and homogenized for 10 to 30 minutes to obtain a surface coating; Applying a surface coating on a release paper with a specific pattern to form a surface coating with a thickness of 3 to 30 microns; The silicone rubber is made into a film and coated on a base fabric to form a base fabric with a silicone rubber layer; The surface coating is laminated to the base fabric with the silicone rubber coating, and then the laminated organic silicone rubber is cured.

10. The preparation method according to claim 9, characterized in that: The curing comprises curing at 80-100° C. for 5-30 minutes and then curing at 130-180° C. for 1-10 minutes.

Citation Information

Cited By

  • Fireproof environment-friendly sealing flexible material and preparation method thereof

    CN121895769A